Effects of Ginger Tea Drinking to Blood Cell Counts of FOLFOX4 Chemotherapy Patients in Colon Cancer - ชีพเจริญรัตน์, นิยม; ทองบ่อ, ชุลีพร; โกมลเมธชัย, กรองแก้ว; เวชกามา, พนิดา; ขันเงิน, ประชาน (Journal of Health Science of Thailand, 2021)
The important problems of the colon cancer patients who received FOLFOX4 chemotherapy were the decrease in blood cell count. The objective of this study was to assess the effects of ginger tea drinking to increase blood cell count in the colon cancer patients who received FOLFOX4 chemotherapy. The study was conducted as an experimental study in the chemotherapy unit of Yasothorn Hospital. There were 24 pateints enrolled in the study. They were divided into 2 groups, 12 each. The experimental group patients received ginger tea 4g/day and the control group patients received placebo. All blood cell counts were compared after receiving chemotherapy for 14 days. It was found that after controlled co-variation, the mean of white blood cell count (WBC) in experimental group was 7.97 x103cell/cu.mm and control group was 7.25 x103cell/cu.mm (p=0.031). Mean of absolute neutrophil count (ANC) in experimental group was 4,943 cell/cu.mm and control group was 4,374 cell/cu.mm (p=0.041). Mean of total lymphocyte count (TLC) in experimental group was 2,457 cell/cu.mm and control group was 2,284 cell/ cu.mm (p=0.144). Mean of Hemoglobin (Hb) in experimental group was 11.55 g/dl and control group was 11.26 g/dl (p=0.064). Mean of platelet counts was 226.12 x103cell/cu.mm and control group was 214.82 x103cell/cu.mm (p=0.226). In conclusion, ginger tea could significantly increased WBC counts and ANC in the colon cancer patients who received FOLFOX4 chemotherapy.